2012
DOI: 10.5897/ajar12.022
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in coleoptile or mesocotyl lengths of upland rice (Oryza sativa L.) and seedling emergence in deep sowing

Abstract: Rain-fed upland rice (Oryza sativa L.) is one of the important crops in Sub-Saharan Africa (SSA) accounting for over 40% of the area under rice cultivation. In SSA, upland rice is primarily established by dry direct seeding (DS), which saves time and labour, although DS is associated with poor seedling emergence and establishment. It is thought that coleoptile and mesocotyl elongation in rice seedlings enhance emergence in deep sowing. A screen house study was conducted from May to December 2011 at Tokyo Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Lee et al (2002) recommended a 2–3-cm sowing depth for japonica rice. When the seeding depth is >3 cm, seedling emergence was markedly delayed (Kawatei et al 1963; Murai et al 1995; Luo et al 2007; Chung 2010; Alibu et al 2012). Moreover, when seeds were sown deeper than 5 cm, the first leaf developed under the soil surface, and seedling establishment decreased remarkably (Chung 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al (2002) recommended a 2–3-cm sowing depth for japonica rice. When the seeding depth is >3 cm, seedling emergence was markedly delayed (Kawatei et al 1963; Murai et al 1995; Luo et al 2007; Chung 2010; Alibu et al 2012). Moreover, when seeds were sown deeper than 5 cm, the first leaf developed under the soil surface, and seedling establishment decreased remarkably (Chung 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mesocotyl and coleoptile lengths are directly related with seedling emergence in deep seeding and enhanced mesocotyl or coleoptile elongation is associated with better seedling emergence and establishment (Turner et al 1982; Murai et al 1995; Luo et al 2007; Chung 2010; Alibu et al 2012). Murai et al (1995) reported that a relationship exists between seedling emergence ability and lengths of leaf, mesocotyl, coleoptile, and leaf internode using dwarf lines under 7 cm soil depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The redabsorbing pigment in maize had an interaction with the phytochrome in the inhibition of mesocotyl growth (Vanderhoef Fig. 1 The diagram of rice mesocotyl elongation influenced by light (Vanderhoef and Briggs 1978;Jones et al 1991;Cao et al 2005), temperature (Gray et al 1998;Chen et al 2005;Gao et al 2006;Tian et al2009), water (Takahashi 1978), and sowing depth (SD) (Alibu et al 2012;Lee et al 2002;Turner et al 1982). SD1, SD2 and SD3 indicated the different sowing depths, in an order of SD3 > SD2 > SD1…”
Section: Major Environmental Factors Affecting Mesocotyl Elongationmentioning
confidence: 99%
“…Previous studies indicated that long mesocotyl was beneficial for the rate and uniformity of seedling emergence (Turner et al 1982;Mgonja et al 1993;Chung 2010). The genotypes with long mesocotyl have stronger germination dynamics and higher rate of seedling emergence than those with short ones (Zhang et al 2005;Alibu et al 2012). Thus, mesocotyl length has been proposed as a key trait in developing rice varieties for dry directseeding rice.…”
Section: Introductionmentioning
confidence: 99%